Genome-Based Taxonomic Rearrangement of the Order Geobacterales Including the Description of Geomonas azotofigens sp. nov. and Geomonas diazotrophica sp. nov. - Xu, Zhenxing; Masuda, Yoko; Wang, Xueding; Ushijima, Natsumi; Shiratori, Yutaka; Senoo, Keishi; Itoh, Hideomi (Frontiers in Microbiology, 2021)
Geobacterales is a recently proposed order comprising members who originally belonged to the well-known family Geobacteraceae, which is a key group in terrestrial ecosystems involved in biogeochemical cycles and has been widely investigated in bioelectrochemistry and bioenergy fields. Previous studies have illustrated the taxonomic structure of most members in this group based on genomic phylogeny; however, several members are still in a pendent or chaotic taxonomic status owing to the lack of genome sequences. To address this issue, we performed this taxonomic reassignment using currently available genome sequences, along with the description of two novel paddy soil-isolated strains, designated Red51T and Red69T, which are phylogenetically located within this order. Phylogenomic analysis based on 120 ubiquitous single-copy proteins robustly separated the species Geobacter luticola from other known genera and placed the genus Oryzomonas (fam. Geobacteraceae) into the family ‘Pseudopelobacteraceae’; thus, a novel genus Geomobilimonas is proposed, and the family ‘Pseudopelobacteraceae’ was emended. Moreover, genomic comparisons with similarity indexes, including average amino acid identity (AAI), percentage of conserved protein (POCP), and average nucleotide identity (ANI) showed proper thresholds as genera boundaries in this order with values of 70%, 65%, and 74% for AAI, POCP, and ANI, respectively. Based on this, the three species Geobacter argillaceus, Geobacter pelophilus, and Geobacter chapellei should be three novel genera, for which the names Geomobilibacter, Geoanaerobacter, and Pelotalea are proposed, respectively. In addition, the two novel isolated strains phylogenetically belonged to the genus Geomonas, family Geobacteraceae, and shared genomic similarity values higher than those of genera boundaries, but lower than those of species boundaries with each other and their neighbors. Taken together with phenotypic and chemotaxonomic characteristics similar to other Geomonas species, these two strains, Red51T and Red69T, represent two novel species in the genus Geomonas, for which the names Geomonas azotofigens sp. nov. and Geomonas diazotrophica sp. nov. are proposed, respectively.